Comparing the risk management standpoint between the project participants for the urban road transport projects in Hanoi - Nguyen Quoc Toan; Nguyen Thi Thuy; Dinh Tuan Hai; Pham Xuan Anh (Archives of Civil Engineering, 2022)
The transport system is considered the “backbone” of the urban development. Along with the rapid economic development, the urban road transport system is being paid attention and invested by Hanoi city. By the year 2050, The Hanoi municipal government is expected to complete and hand over for use about 317 urban road transport projects. Due to the high demands of social and economic efficiency, the urban road transport projects in Hanoi face many risks. In which, there are 13 high dangerous risks for the urban road transport project in Hanoi. These risks have the high probability and severity impacted on the outcome of the projects. The project participant’s risk management standpoint will determine the solutions to respond the respective risks, thereby affecting the results of the project. In this paper, the authors compare the risk management standpoint of three main project participants, including owner/project management board, consultant and main contractor/subcontractor. The difference of the risk management standpoint is shown clearly by the project participants’ assessments of 13 high dangerous risks.